Bee venom phospholipase A2 alleviates collagen-induced polyarthritis by inducing Foxp3+ regulatory T cell polarization in mice - Gwang-Muk Choi (Nature Portfolio, 2021)
Abstract The mechanism underlying bee venom (BV) therapy is still controversial, with opinions ranging from constituent-based pharmacological action to homeopathic-like activity. The purpose of this study was to examine whether BV phospholipase A2 (bvPLA2), an enzymatic component of BV, is a novel anti-inflammatory and anti-arthritic mediator capable of stimulating CD25+ Foxp3+ regulatory T cell (Treg) polarization in a mouse model of human rheumatoid arthritis (RA). An experimental model of RA was established in male DBA/1 mouse by 2-week-interval injections of 100 μg type II collagen emulsified in complete (first injection) or incomplete Freund’s adjuvant (second injection) at the base of the tail. During arthritis development, bvPLA2 (0.1, 0.5, 1.0 mg/kg) and/or Treg inhibitors such as anti-CD25 antibodies and peptide 60 (P60) were injected intraperitoneally for 5 weeks. Arthritic symptoms and the expansion of Tregs were then assessed by behavioral assessments, histological and micro-CT imaging, and flow cytometry. bvPLA2 injections significantly alleviated arthritic behaviors such as squeaking and joint swelling, consistent with changes seen on both histological and micro-CT images. The anti-arthritic effects of bvPLA2 were blocked by intraperitoneal injections of 0.25 mg/kg anti-CD25 antibody and 10 μg/kg P60, as determined by behavioral assessments. Flow cytometric analysis of dendritic cells, B cells, and major T cell subsets from spleens revealed a significant depletion of Tregs following anti-CD25 antibody, but not P60, treatment. bvPLA2 treatment exerted significant anti-inflammatory and anti-arthritic activities in a mouse model of RA via the induction of Tregs.